Comparative study of zeolite A synthesis in batch and semibatch reactors - Mat, Ramli (Faculty of Chemical & Natural Resources Engineering, 1993)
Synthesis of zeolite A from natrium silicate and natrium aluminate solutions were studied using batch and semibatch reactors. Sample were taken at one hour interval times. Solid samples were analyzed using X-ray Diffraction (XRD), Scanning Electron Microscope (SEM), and Malvern Mastersizer. Performance of both mode of operations were compared. Semibatch process produced zeolite A faster and larger than those of batch process. Scanning Electron Micro graph of the solid sample indicated a change in the crystal habitat and size due to change in the mode of operation.